The impact of immigration on the educational attainment of natives - Jennifer Hunt (Institute for the Study of Labor (IZA), 2012)
Using a state panel based on census data from 1940-2010, I examine the impact of immigration on the high school completion of natives in the United States. Immigrant children could compete for schooling resources with native children, lowering the return to native education and discouraging native high school completion. Conversely, native children might be encouraged to complete high school in order to avoid competing with immigrant high-school dropouts in the labor market. I find evidence that both channels are operative and that the net effect is positive, particularly for native-born blacks, though not for native-born Hispanics. An increase of one percentage point in the share of immigrants in the population aged 11-64 increases the probability that natives aged 11-17 eventually complete 12 years of schooling by 0.3 percentage points, and increases the probability for native-born blacks by 0.4 percentage points. I account for the endogeneity of immigrant flows by using instruments based on 1940 settlement patterns.
Keywords: J15; I21; 330; immigration; education; Internationale Wanderung; Migranten; Bildungsverhalten; Wettbewerb; Bildungsniveau; USA